Assessment of Mangrove Functions in Supporting Coastal Ecosystem Sustainability in Tambak Gojoyo Hamlet, Wedung Village, Wedung District, Demak Regency - Cahyo Wulandari; Andini Cahya Alifiany; Isna Kamalia (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Mangrove ecosystems contribute significantly to coastal ecosystems through their functions as natural barriers against abrasion and seawater intrusion, carbon absorbers, and providers of resources that support the livelihoods of coastal communities. However, land conversion, infrastructure development, and rising sea levels have caused a decline in the extent and quality of mangroves in Demak Regency, including Dukuh Tambak Gojoyo, which is vulnerable to tidal flooding and habitat degradation. This condition directly affects the economy of communities dependent on fisheries and aquaculture, thus requiring conservation efforts integrated with community-based empowerment. This community service program aimed to increase public awareness, skills, and participation in sustainable mangrove management through educational, practical, and collaborative approaches. The methods used included field surveys, interviews, nursery experiments, socialization, planting, and practical utilization of mangrove products. The program produced four main outcomes: (1) Eco-Grow-based mangrove nurseries with propagule immersion treatment using auxin hormones, which produce healthier and faster-growing Rhizophora apiculata seedlings; (2) Mangrove planting to support the Mageri Segoro program; (3) Introduction of mangrove species through barcode name boards (M-Smart) as a means of conservation education; and (4) Utilization of mangrove propagules as natural dyes with school students, which effectively enhanced their understanding and creativity in utilizing natural resources in an environmentally friendly way. Overall, this activity demonstrates that participatory and innovative approaches can foster environmental awareness, encourage collaboration, and provide ecological, social, and economic benefits for the sustainability of coastal communities